Physical mobility of stroke patients in the home: a proposed concept - Rafaella Pessoa Moreira; Thelma Leite de Araujo; Lorita Marlena Freitag Pagliuca (Universidade Federal do Ceará, 2013)
The aim of the present study was to construct a concept of mobility limitation in the home, based on the identification of antecedents, attributes, and consequences in stroke patients. It accomplished the concept analysis of the literature starting from access on-line to three databases, in October month 2009. It used descriptors Mobility Limitation and Stroke in the English, Portuguese and Spanish languages. It was found 140 articles and selected 13. The main antecedents identified were: stroke, decreased muscle strength in the lower limbs, and loss of balance; attributes: impaired walking ability and decreased walking speed; consequences: decreased quality of life, decreased participation in society, decrease in activities of daily living and instrumental activities of daily living, and falls. This search might support the future creation of tools for use in studies on this subject and will enable nurses to better focus their practice for the care of these patients.